GAME TEORY AND ECONOMIC SKILLS: EXPLORING LITERACY NEEDS FOR STRATEGY BUSINESS ENTREPRENEURSHIP IN THE DIGITAL ERA - Nanang Handoko; Pompong Budi Setiadi, Sri Rahayu (Adisam Publisher, 2025)
This article examines literacy skills in facing the challenges of entrepreneurial management in the technological era. Digital literacy skills play an important role in the existence of entrepreneurship today. Entrepreneurial management is currently facing new challenges with a situation of change from the traditional to the modern era, namely the all-digital era. Exploring entrepreneurial management knowledge is very vital in today's entrepreneurial world to achieve its goals, opportunities and challenges. entrepreneurial skills Entrepreneurship as a part of economics that involves the good use of management strategies and economic principles. This article examines exploring entrepreneurial management strategies for literacy skills in entrepreneurial management based on a creative and innovative economy adapting to changes. In this research, entrepreneurial management strategies with creative and innovative digitalization skills are very important. The method has been used with a literature review as a type of descriptive research as well as a qualitative assessment. The data was generated from a review of the results of previous research papers. The analysis method is carried out through game the stages of collecting research data, reducing research data, presenting research data, then drawing conclusions from the research results. This research produces an analysis that shows that literacy skills are capital for implementing entrepreneurial management ,analysis that shows that as capital for implementing entrepreneurial management with entrepreneurial management strategy skills, namely aspects of game teory ,financial literacy, economic literacy, managerial literacy, decision making. and problem solving